Cytoprotective Role of Alpha-1 Antitrypsin in Vascular Endothelial Cell Under Hypoxia/Reoxygenation Condition. Issue 1 (July 2015) - Feng, Yaling; Hu, Lingqing; Xu, Qian; Yuan, Hua; Ba, Linlin; He, Yue; Che, Haisha
Abstract : Abstract: Ischemia/reperfusion (IR) injury is a critical factor in the pathogenesis of tissue injury after myocardial infarction, multiple organ failure, and other acute ischemic events. Previous studies suggest that α1-antitrypsin (AAT) plays a cytoprotective role in beta cells and human pulmonary cells. We hypothesize that AAT may have the potential to reduce IR-induced vascular injury involved in cell apoptosis and permeability. In this study, we investigate the role of AAT in human umbilical vein endothelial cells using a model wherein endothelial cell monolayers are exposed to hypoxia/reoxygenation (HR). We found that exogenous AAT alleviated HR injury in a dose- and time-dependent manner. Furthermore, by gain and loss function experiments, we demonstrated that overexpression of AAT decreased cell apoptosis and promoted proliferation by inhibiting Rac1/PAK/p38 signaling and against oxidative stress, and also reduced cellular permeability by increasing ZO-1 and occludin expression. Thus, we provided evidences to illustrate that AAT played a cytoprotective role in vascular endothelial cell under HR condition, suggesting that AAT treatment may be therapeutically beneficial to reduce IR-induced vascular injury.